Odpowiedź:
Szczegółowe wyjaśnienie:
2⁵ * 4³ : 8³ = 2⁵ * (2²)³ : (2³)³ = 2⁵ * 2⁶ : 2⁹ = 2¹¹ : 2⁹ = 2² = 2 * 2 = 4
125⁵ : (25⁴ * 5⁶) = (5³)⁵ : [(5²)⁴ * 5⁶)] = 5¹⁵ : (5⁸ * 5⁶) = 5¹⁵ : 5¹⁴ = 5¹ = 5
[tex]\frac{9^{6}*27^{5} }{81^{7} } = \frac{(3^{2})^{6} *(3^{3})^{5} }{(3^{4})^{7} } = \frac{3^{12}*3^{15} }{3^{28} } = \frac{3^{27} }{3^{28} } =[/tex] [tex]3^{-1}[/tex] = ( ⅓)¹ = ⅓
0,2¹³ * 5⁶ * 5⁷ = (⅕)¹³ * 5⁶ * 5⁷ = [tex]5^{-13}[/tex] * 5⁶ * 5⁷ = 5⁰ = 1
0,1⁶ * (10²)³ = ([tex]\frac{1}{10}[/tex])⁶ * 10⁶ = [tex]10^{-6}[/tex] * 10⁶ = 10⁰ = 1
(2⁷)⁴ * 0,5²⁵ = 2²⁸ * (½)²⁵ = 2²⁸ * [tex]2^{-25}[/tex] = 2³ = 2 * 2 * 2 = 8